1998
DOI: 10.1902/jop.1998.69.9.1008
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Periodontal Ligament Cells to Fibronectin

Abstract: Fibronectin (fn) is an extracellular matrix (ECM) molecule important in cell adhesion and migration and in wound healing. It is also likely important in periodontal ligament (PDL) cell-ECM interactions, and thus in regenerating periodontal tissues. In this study we characterized PDL cells and their interactions with FN, testing different PDL cell isolates taken from healthy and diseased conditions. PDL cells were characterized by their morphology, integrin profile, motility, and bone nodule formation. Cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 50 publications
7
53
0
2
Order By: Relevance
“…Likewise, proteolytic fragmentation of fibronectin may result from proteolysis by such MMPs as MMP1, -2, and -3, or by elastase (Wysocki and Grinnell, 1990;Grinnell and Zhu, 1994;Fukai et al, 1995). The resulting peptides regulate several cellular functions, including cell proliferation, chemotaxis (Kapila et al, 1998), migration (Schor et al, 1999), apoptosis (Kapila et al, 1999), and MMP expression in a manner that differs from that of the full-length native molecule. For example, in synovial fibroblasts, fibronectin fragments, but not intact fibronectin, can induce MMP-1 and MMP-3 expression by signaling through the oa5il1 integrin (Werb et al, 1989;Damsky et al, 1992;.…”
Section: (F) Proteolytic Degradation Of Ecm Molecules Regulates Mmp Ementioning
confidence: 99%
“…Likewise, proteolytic fragmentation of fibronectin may result from proteolysis by such MMPs as MMP1, -2, and -3, or by elastase (Wysocki and Grinnell, 1990;Grinnell and Zhu, 1994;Fukai et al, 1995). The resulting peptides regulate several cellular functions, including cell proliferation, chemotaxis (Kapila et al, 1998), migration (Schor et al, 1999), apoptosis (Kapila et al, 1999), and MMP expression in a manner that differs from that of the full-length native molecule. For example, in synovial fibroblasts, fibronectin fragments, but not intact fibronectin, can induce MMP-1 and MMP-3 expression by signaling through the oa5il1 integrin (Werb et al, 1989;Damsky et al, 1992;.…”
Section: (F) Proteolytic Degradation Of Ecm Molecules Regulates Mmp Ementioning
confidence: 99%
“…Under these conditions, an altered matrix can result from proteolytic cleavage or alternative splicing of matrix molecules. In inflammation, proteolysis of extracellular matrix molecules leads to the formation of fragments, such as fibronectin (FN) 1 fragments, that elicit cellular responses different from those elicited by the intact molecule (1)(2)(3)(4)(5). For example, disease-associated fragments of FN trigger p53-mediated apoptosis of primary cells, but the intact molecule does not (6 -8).…”
mentioning
confidence: 99%
“…FN and COLL1 are components of the extracellular matrix (ECM) in the PDL (Lukinmaa et al 1991), and are considered markers for fibroblastic cells (Hou and Yaeger 1993). It has been reported that FN increases the proliferation rate of PDL cells (Kapila et al 1998), which led to the suggestion that FN is associated with PDL regeneration, although the functions of FN in the PDL are virtually unknown. OPN exists in many tissues, and is a component of the bone ECM.…”
Section: Discussionmentioning
confidence: 99%